1987
DOI: 10.1038/hdy.1987.111
|View full text |Cite
|
Sign up to set email alerts
|

Variation in allele frequencies in the outcross pollen pool of Eucalyptus regnans F. Muell. throughout a flowering season

Abstract: Individual trees within a stand of Eucalyptus regnans were found to vary in fecundity and time of flowering. Allele frequencies at three enzyme loci were estimated for the outcross pollen pool taking these differences into account, and were found to vary with time. These frequencies were compared to those estimated using methods that assume allele frequencies in outcross pollen pools are constant throughout a flowering season. For times when the bulk of trees were in flower the allele frequencies estimated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Temporal heterogeneity in gene frequencies of gamete and zygote pools can be induced by variation in flowering time or fecundity within a population (Gregorius et at., 1986;Fripp et al, 1987;Sampson et *Correspondence. at., 1990). Differentiation on a relatively small scale, loss of alleles caused by genetic drift and/or a certain amount of inbreeding may appear within populations as a consequence of the different types of driving force.…”
Section: Introductionmentioning
confidence: 99%
“…Temporal heterogeneity in gene frequencies of gamete and zygote pools can be induced by variation in flowering time or fecundity within a population (Gregorius et at., 1986;Fripp et al, 1987;Sampson et *Correspondence. at., 1990). Differentiation on a relatively small scale, loss of alleles caused by genetic drift and/or a certain amount of inbreeding may appear within populations as a consequence of the different types of driving force.…”
Section: Introductionmentioning
confidence: 99%
“…(1986) found that temporal variation in the allele frequencies of the pollen pool may have contributed to low estimates of I at two marker loci that themselves affect time of flowering or are associated with alleles of loci that affect time of flowering. In contrast, Fripp et al (1987) found no evidence of biased single-locus I estimates due to the demonstrated temporal heterogeneity of allele frequencies in E. regnans.…”
Section: Discussionmentioning
confidence: 47%
“…A similar observation was made for an isolated stand of the mass flowering forest tree E. regnans (Fripp et al, 1987).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations